Pengaruh Jenis dan Konsentrasi Filler terhadap Karakteristik Bioplastik dari Tepung Maizena - Hutabalian,, Parngoluan; Harsujowono, Bambang Admadi; Hartati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This study aims to determine the effect of filler types and concentrations and their interactions on the characteristics of bioplastics and to determine the concentrations and types of fillers that produce bioplastics with the best characteristics. This research used factorial randomized block design. The first factor is the type of filler consisting of 3 levels that is ZnO, clay, CaCO 3 . The second factor is the filler concentration consisting of 3 levels 0, 3, 6, and 9% (w/w). Each treatment are grouped into two time-based of making bioplastics, so there are 24 experimental units. The variabels observed were tensil strength, elongation at break, modulus young, swelling, and biodegradation. The data obtained were analyzed of variant and test Tukey’s. The results showed that the concentration and type of filler had a very significant effect on tensile strenght, elongation at break, modulus young and swelling but had no significant effect on the biodegradation value. The 9% concentration with ZnO filler produced the best bioplastic characteristics with a tensile strength value  4.11 MPa, elongation at break 31.16%, modulus young 7.06 MPa, swelling 55.01%, and biodegradability for 6-7 days.  Keywords: Bioplastics, filler concentration, ZnO, clay, CaCO 3